Examining the moderating role of firm reputation on the relationships between supply chain quality management practices and organizational performance of manufacturing firms in Ghana - Edzi, Daniel Tony (KNUST, 2024)
A thesis submitted to the department of supply chain and information systems, institute of distance learning, in partial fulfilment of the requirement for the award of the degree of master of science (procurement and supply chain management)